EVALUASI KINERJA RUAS JALAN KI HAJAR DEWANTARA KOTA TERNATE - Ilyas B Ibrahim; Chairul Anwar; Muhammad Taufiq Yudha Saputra (Journal of Science and Engineering, 2018)
The position of Ki Hadjar Dewantara road is strategic location, where as an education center, office and residential center are often happened to increase in vehicle volume, especially during peak hour, consequently, this condition makes congestion on this road. There are ideas for road widening, moved side barriers and one.way traffic management, which are purposing to know traffic performance currently and generating a recommendation of traffic systems. By observations on traffic surveys were carried out on the road at 06.00 to 18.00 WIT. Traffic performance analysis is based on the 1997 Indonesia Road Capacity Manual (MKJI). The results of the Ki Hajar Dewantara road analysis showed a high level of side resistance with a value of degree of saturation (DS) in segment 1, which was 0.78, free flow speed of 31.2 km / hour, road capacity of 1953 pcu / hour. Furthermore, as an alternative solution the application of a one way system on the road section that showed a better performance with DS = 0.32 for west to east and DS = 0.22 east to west with a service level B category with stable current, speed slightly limited by traffic, the driver has enough freedom to choose a speed. The design for implementing this one-way system is good for solving problems.